Some of the best moral theories to guide health practitioners in South Africa amid growing less moral at health care institutions (African Journal of Biomedical Research, 2024)
Moral theories play an important role in the shape of health care institutions and health practitioners. Health practitioners are constantly confronted ethical dilemmas and work over burden due to high population and migration of foreign nationals in South Africa. Various moral theories such as deontology, consequentialism and virtue ethics provide framework to guide these choices. In the health setting, understanding, and applying these theories ethically is essential for preserving patients’ rights, ensuring equitable care, and maintaining professional integrity